GOVERNMENTAL LIABILITY IN ORGANIZING ADMINISTRATION FUNCTION IN INDONESIA - Asep Hidayat (Bajang Institute, 2021)
This research is motivated by the fact that in the State and society, it is still far from expectations; of course, this should be accountable by the government to the people who have voted for it because they have contributed their voices and in other aspects, the community has handed over their power and authority to the government. The problem in this research is that the government's accountability to the community is still low. The purpose of this study is to identify and describe the duties and functions of accountable government administration. This study uses a normative juridical qualitative approach based on legislation. Data collection techniques used are documentation/library studies. The results showed that the function of government administration was not optimal, so it had an impact on the level of public trust in the government.